2002
DOI: 10.1177/156482650202300110
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Short Food-Frequency Questionnaire for Screening Women of Childbearing Age for Vitamin A Status in Northwestern Iran

Abstract: A high percentage of women in their childbearing years suffer from subclinical vitamin A deficiency; 10% to 20% of pregnant women worldwide are vitamin A deficient. This study aimed to design and validate a short food-frequency questionnaire to serve as a simple screening tool for vitamin A status in women of childbearing age. The sample consisted of 187 healthy, nonpregnant, nonlactating women 15 to 49 years of age, from urban and rural areas of Marand district in East Azerbaijan. Dietary intake was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Using the WHO cut-offs for national prevalence of vitamin A deficiency, Iran should by this standard be considered a country with severe vitamin A insufficiency prevalence (<0.7 µmol/L) in 2001. In contrast, reports from the north of Iran, Marand district, in 2002 showed that 2.1% of child-bearing women had a deficiency level of vitamin A (<0.7 µmol/L) but 18% had values between insufficient or suboptimal level of vitamin A (19). Prevalence of deficiency levels (<0.36 µmol/L) was 6.6% nation-wide and similar to the average global prevalence of maternal vitamin A deficiency in developing countries (7%) (20).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using the WHO cut-offs for national prevalence of vitamin A deficiency, Iran should by this standard be considered a country with severe vitamin A insufficiency prevalence (<0.7 µmol/L) in 2001. In contrast, reports from the north of Iran, Marand district, in 2002 showed that 2.1% of child-bearing women had a deficiency level of vitamin A (<0.7 µmol/L) but 18% had values between insufficient or suboptimal level of vitamin A (19). Prevalence of deficiency levels (<0.36 µmol/L) was 6.6% nation-wide and similar to the average global prevalence of maternal vitamin A deficiency in developing countries (7%) (20).…”
Section: Discussionmentioning
confidence: 94%
“…A low access in the south of Iran to main sources of vitamin A (dairy products, vegetables, and fruits) may be related to the hot and dry climate in this region (27). One study in northwest of Iran showed that the important sources of vitamin A in child-bearing women were nuts and green leaves, products that were not typical of other populations (19). Vegetables and fruits provide carotenoids equivalent to more than 50% of vitamin A (4).…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of fruits and vegetables are grown and consumed and meat, poultry and fish are highly valued, but relatively expensive. Nuts and fresh leafy greens, including plants used in other cuisines as herbs in small quantities, are consumed regularly and in quantities that make important contributions to nutrient intake 11 . Tea is the major beverage.…”
Section: Food Consumptionmentioning
confidence: 99%
“…Subjects were assisted to remember all consumed meals and food items, as well as their amounts. Both forms were previously validated for Iranian foods (26). Nutritionist 4 Software (San Bruno, CA) was used to estimate daily dietary intake amounts.…”
Section: Dietary Assessmentmentioning
confidence: 99%